Kontribusi Frekuensi, Fasilitas, Dan Lingkungan Belajar Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP N 2 Wonogiri - Rohmandani, Nurul, Prof. Dr. Sutama, M.Pd (2017)
This research includes four objectives that was used. 1) To test contribution frequency, facilities and learning environment of the mathematics learning outcomes. 2) To test contribution of learning frequency of the mathematics learning outcomes. 3) To test contribution of learning frasility of the mathematics learning outcomes. 4) To test contribution of learning environment of the mathematics learning outcomes. Type of this research is quantitative with expost facto design. The population of the entire research grade VIII SMP N 2 Wonogiri as much as 263 students and samples used as many as 159 students. Engineering data collection method using question form and documentation. Analysis of the multiple linear regression using the test. The results of this research were. 1) There was contribution frequency, facilities and learning environment of the mathematics learning outcomes in a significant way of 9,18%. 2) There was contribution frequency learning of the mathematics learning outcomes with only donate 4,26%. 3) There was no contribution of learning facilities of the mathematics learning outcomes with only donate 0,035%. 4) there was contribution towards a learning outcomes learning environment for mathematics in signfiikan for 4,88%. Keywords: mathematics learning outcomes, frequency learning, learning facility, learning environment